The Satisfaction of Entrepreneurs in Terengganu Private Limited Companies toward the Concept of Corporate Entrepreneurship: A Descriptive Analysis - Halim, Muhammad Abi Sofian Abdul; Yahya, Hasyaniza; Mahmud, Syahrul Hezrin; Zainab, Fatimah (Journal of Asian Business Strategy, 2011)
This study will determine the level of satisfaction among Terengganu private limited companies towards the concept of corporate entrepreneurship, in a context of; corporate venturing, strategic renewal, and internalization. The study was based on a survey carried out from the questionnaire that is administered involving 105 private limited companies which are operated their business in Terengganu. By using the descriptive analysis on the level of satisfaction among the Terengganu private limited companies towards the concept of corporate entrepreneurship are examined. The findings show that most of entrepreneurs in Terengganu private limited companies are satisfied toward the factors of corporate venturing, strategic renewal and internalization. Conversely, the interpretation of this results show that most of Terengganu private limited companies are satisfied and really practiced the concept of corporate venturing and strategic renewal. Furthermore, the findings of this study also will help the Terengganu state government to evaluate the quality standard of private limited companies toward the concept of corporate entrepreneurship.